Współdziałanie nauki i przemysłu na przykładzie Wrocławskiego Parku Technologicznego S.A. - Szczerbak, Julianna; Ageyeva, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Pro-innovative institutions, namely science and technology parks, incubators and technology transfer centers constitute a crucial component of the innovation system of each country. They are responsible for the swift knowledge and innovation transfer, which ensures the generation of external benefits being the basis of the economic growth based on knowledge. One of the most vital relations in the innovation system is the cooperation of the science sector and business: innovation and technological development of a particular country depends on the functioning of this collaboration. In Poland exists a considerable number of pro-innovative institutions that are to create various channels of technology and innovation transfer between the science-research sector and industry. These institutions operate within different territorial, organizational, property and functional systems. Various types of these organizations try to meet the variety of needs that arise in relation to the innovation system and to customers’ demands of different kinds. The institutions are relatively young as they are still organizing themselves, gathering material resources and experiences in network creation. The majority of such associations was established in the late 90s and at the beginning of the 21st century. The foundation of the younger ones was described in this paper. Among the most important matters brought up are the ways of support offered by technology parks. In 1998 Wrocław Technology Park was set up. It aims to transfer new technologies to the already existing and newly-established business entities and to perform research-development and implementation works in the field of biotechnological and technical sciences. By creating projects such as “Nutribiomed” or “From Wrocław Technology Park to Innopolis Wrocław” WPT facilitates the utilization of the scientific and industrial potential of Wrocław and the region and also stimulates the progress of the advanced technology industry.
Keywords: współpraca; nauka; przemysł; Wrocławski Park Technologiczny S.A.